Pengaruh Return On Assets (ROA), Debt To Equity Ratio (DER), Dan Earning Per Share (EPS), Terhadap Harga Saham Yang Terdaftar Di Bei Periode 2015-2019 - Maria Juliani; Feby Siska Sembiring; Januardin Januardin (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Banking in Indonesia in general has a function as a place to collect funds from the public in the form of savings and distribute them again to the public in the form of credit or other forms in order to improve the standard of living of many people. This study aims to determine whether Return On Assets (ROA), Debt to Equity Ratio (DER) and Earning Per Share (EPS) have a positive or negative influence on stock prices in banking companies. There are 46 banking companies listed on the BEI and this study uses a purposive sampling technique as many as 24 companies that list their share prices for the 2015-2019 period. The results of this study are that increasing ROA has a significant negative effect on rising stock prices, DER has a significant negative effect on stock prices, and EPS has a significantly positive effect on stock prices. Keywords: Return On Assets (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Stock Price.